2014
DOI: 10.1007/s00268-014-2606-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Robotic Thyroid Surgery in South Korea: A Web‐Based Survey

Abstract: Opinions differed regarding the advantages and disadvantages of two approaches for RoT. This may be due to differences in surgical procedure itself between two approach methods. Accumulation of RoT surgeon's experiences might establish consensus regarding patient selection and indications for the RoT will need to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Because there are distinct advantages to remote‐access robotic thyroid surgery, including the lack of visible scarring in the neck region and the ability to perform precise surgical manipulations in the narrow working space, these procedures are widely performed . BABA is a prevalent remote‐access procedure used in robotic thyroid surgery and has excellent cosmetic results with surgical and oncologic safety.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are distinct advantages to remote‐access robotic thyroid surgery, including the lack of visible scarring in the neck region and the ability to perform precise surgical manipulations in the narrow working space, these procedures are widely performed . BABA is a prevalent remote‐access procedure used in robotic thyroid surgery and has excellent cosmetic results with surgical and oncologic safety.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent cosmetic outcomes and reductions in pain and dysphagia have also been reported with this technique (17)(18)(19)(20)(21). Robotic thyroid surgery is particularly prevalent in Korea, where more than 8,000 cases of robotic thyroidectomy were performed from 2007 to 2011 (2,000 procedures in 2011 alone) (22).…”
Section: Introductionmentioning
confidence: 90%
“…However, the surgical indications for robotic thyroidectomy have expanding as surgeons' experience levels have increased. A recent web-based survey conducted by Bae et al reported that the main indications for robotic thyroidectomy were papillary thyroid cancers <2 cm in size, intracapsular lesions, a non-posterior location, and no clinical evidence of lateral LN metastasis (22).…”
Section: Surgical Indications For Robotic Thyroidectomymentioning
confidence: 99%
See 1 more Smart Citation
“…[2] For the treatment of this condition, open thyroidectomy is performed worldwide with low morbidity and mortality. [3] Thyroidectomy is associated with relatively moderate pain; therefore, many patients require pain control and management during the early postoperative phase, [4,5] and the pain can progress to a chronic form. Patient-controlled analgesia (PCA), which allows patients to self-administer pain medications, is known to control postoperative pain efficiently.…”
Section: Introductionmentioning
confidence: 99%